The efficacy of mesalazine on nonspecific terminal ileal ulcers: A randomized controlled trial - Li, Junrong; Ling, Fangmei; Guo, Di; Zhao, Jinfang; Cheng, Ling; Chen, Yidong; Xu, Mingyang; Zhu, Liangru (Frontiers in Pharmacology, 2022)
Background : Nonspecific terminal ileal ulcers are one of the common ulcerative diseases in terminal ileum. However, the studies about treatment efficacy are scarce. We aimed to investigate the efficacy of mesalazine in the treatment of this disease. Methods : Eighty-two patients with nonspecific terminal ileal ulcers who sought outpatient medical treatment in the Division of Gastroenterology, Wuhan Union Hospital, from April 2016 to January 2019 were enrolled and randomly divided into two groups. The experimental group took mesalazine orally, 4.0 g / d, once a day for 3 months. The control group was followed up without special intervention. The primary endpoint was the endoscopic remission rate at the 6th and 12th month. Secondary endpoints included the clinical remission rate at the 1st, 6th and 12th month and adverse events (ChiCTR1900027503) . Results : About the endoscopic efficacy, the remission rate of the experimental group and control group was 73.2% versus 61.0% at the 6th month (RR=1.20, 95%CI 0.88~1.63, p=0.24) and 87.8% versus 78.0% at the 12th month (RR=1.13, 95%CI 0.92~1.37, p=0.24). About the clinical efficacy, the remission rate was 70.3% versus 43.8% at the 1st month (RR=1.61, 95%CI 1.03~2.51, p=0.03), 83.8% versus 68.8% at the 6th month (RR=1.22, 95%CI 0.93~1.60, p=0.14) and 91.9% versus 81.3% at the 12th month (RR=1.13, 95%CI 0.93~1.37, p=0.34). During follow-up, no patients were diagnosed with Crohn's disease or intestinal tuberculosis, and no patients developed significant complications. Conclusions : For patients with nonspecific terminal ileal ulcers, there is no disease progression over a short term.In addition, there is no significant difference in clinical or endoscopic efficacy between patients who received mesalazine and patients who are followed up without special intervention.